ChemInform Abstract: Energy‐Efficient Degradation of Rhodamine B in a LED Illuminated Photocatalytic Fuel Cell with Anodic Ag/AgCl/GO and Cathodic ZnIn2S4 Catalysts. Issue 16 (March 2016) - Liu, Yuanyuan; Liu, Lifen; Yang, Fenglin
Abstract: Stainless steel electrodes loaded with anodic Ag/AgCl/graphene oxide (GO) and cathodic ZnIn2 S4 are used in a one‐chambered photocatalytic fuel cell (PFC) for rhodamine B (RhB) degradation under visible light (2 W LED).